DAMPAK GREEN FINANCE TERHADAP PERTUMBUHAN EKONOMI SYARIAH - Ghaniiy Al Hamiid; M Nathan bari Harahap (Journal of Islamic Economics and Finance, 2025)
Green finance was a financial instrument designed to support environmentally friendly and sustainable economic activities. This concept became increasingly relevant amid the growing global awareness of climate change and the importance of environmental conservation. In the context of Islamic economics, green finance not only reflected concern for the environment but also integrated Islamic ethical values that emphasized balance, justice, and sustainability, as embodied in the principles of maqashid sharia. This study aimed to evaluate the impact of green finance on the growth of the Islamic economy using a systematic literature review approach based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. The findings of this study showed that various instruments such as green sukuk , green financing, and innovations in environmentally oriented Islamic financial products contributed to improving both economic and social performance. Furthermore, green finance in Islamic economics also helped shape an inclusive and sustainable financial ecosystem aligned with long-term development goals. Therefore, the integration of green finance into Islamic economic policies and practices was seen as a strategic step in addressing the challenges of sustainable development in the modern era.